2020
DOI: 10.1136/bmjpo-2019-000613
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve quantitative measures of parent satisfaction in neonatal care: a systematic review

Abstract: ObjectiveInterventions improving parent satisfaction can reduce parent stress, may improve parent-infant bonding and infant outcomes. Our objective was to systematically review neonatal interventions relating to parents of infants of all gestations where an outcome was parent satisfaction.MethodsWe searched the databases MEDLINE, EMBASE, PsychINFO, Cochrane Central Register of Controlled Trials, CINAHL, HMIC, Maternity and Infant Care between 1 January 1946 and 1 October 2017. Inclusion criteria were randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…This refined parent experience survey, which focuses on communication and parent involvement, was evaluated to have favourable performance in the neonatal parent population, and can be used to assess parent experience in UK neonatal care. Inconsistency in and lack of validation of survey instruments measuring parent satisfaction in neonatal care (and specifically with family centred care) have been highlighted worldwide 8 14. The lead author’s systematic review of interventions aiming to improve parent experience of neonatal care identified that less than 20% of studies used fully validated surveys 8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This refined parent experience survey, which focuses on communication and parent involvement, was evaluated to have favourable performance in the neonatal parent population, and can be used to assess parent experience in UK neonatal care. Inconsistency in and lack of validation of survey instruments measuring parent satisfaction in neonatal care (and specifically with family centred care) have been highlighted worldwide 8 14. The lead author’s systematic review of interventions aiming to improve parent experience of neonatal care identified that less than 20% of studies used fully validated surveys 8.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistency in and lack of validation of survey instruments measuring parent satisfaction in neonatal care (and specifically with family centred care) have been highlighted worldwide 8 14. The lead author’s systematic review of interventions aiming to improve parent experience of neonatal care identified that less than 20% of studies used fully validated surveys 8. Most surveys are administered around the time of discharge from neonatal care and retrospectively assess parent experience, like the recently developed CO-PARTNER tool, which measures parent participation and collaboration with staff 19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that parent satisfaction can be improved through simple interventions, such as providing written information to parents,11 12 however, previous interventions required additional work from staff to collect, record, collate and provide information to parents, limiting their sustainability and generalisability. Further limitations of previous studies include the failure to involve parents in study development and the use of invalidated questionnaires to measure the impact of interventions 13…”
Section: Introductionmentioning
confidence: 99%